(untitled) (CIPEEX, 2026)
The research aimed to determine the number of trans women victims of domestic violence in the city of Anápolis, as well as to recognize their diverse gender identities. This research was developed through the PIVIT scientific initiation program at the Evangelical University of Goiás. The study analyzed the impacts of the 2022 ruling on Special Appeal (REsp) No. 1977124-SP, by the Superior Court of Justice, which extended the protection of Law 11,340/2006 (Maria da Penha Law) to trans women, recognizing gender identity as a criterion for the law’s application. The methodology involved document analysis, a literature review, and visits to the Anápolis Specialized Women’s Police Station. The results highlighted the lack of specific data on trans victims in the Women’s Police Station records, which makes it impossible to categorize incidents and reinforces the invisibility of these individuals. It was also found that violence against trans women goes beyond the legal field, reflecting structural prejudices and the persistence of a culture that subverts non-cisgender identities.